2016
DOI: 10.1177/0954410016648997
|View full text |Cite
|
Sign up to set email alerts
|

Neural network based dynamic model and gust identification system for the Jetstream G-NFLA

Abstract: Artificial neural networks are an established technique for constructing non-linear models of multi-input-multi-output systems based on sets of observations. In terms of aerospace vehicle modelling, however, these are currently restricted to either unmanned applications or simulations, despite the fact that large amounts of flight data are typically recorded and kept for reasons of safety and maintenance. In this paper, a methodology for constructing practical models of aerospace vehicles based on available fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Some novel parameter identification approaches have been proposed recently. 1215 Particularly, there is a growing interest for parameter identification via deep learning (DL) methods. 16,17 DL is a representation-learning method which can automatically extract multiple levels features of input data by training and has been successfully applied to many fields.…”
Section: Introductionmentioning
confidence: 99%
“…Some novel parameter identification approaches have been proposed recently. 1215 Particularly, there is a growing interest for parameter identification via deep learning (DL) methods. 16,17 DL is a representation-learning method which can automatically extract multiple levels features of input data by training and has been successfully applied to many fields.…”
Section: Introductionmentioning
confidence: 99%
“…46 Available mathematical models for airships do not incorporate atmospheric effects and wind turbulence, 5,16 while such effects for conventional aircraft are well established. 47 It has been reported that identifying a fully parameterized grey-box model of an airship using classical identification technique suffered poor convergence, and thus a model with reduced parameters was employed. 38 In a recent work, grey-box modelling was found to yield inferior performance as compared to black-box approach for an airship.…”
Section: Introductionmentioning
confidence: 99%